Pengaruh Penambahan Lemak Rusa (Cervus Timorensis) Terhadap Umur Daya Simpan Telur Asin dan Bakteri Salmonella - Indrawati Indrawati; Syetiel Maya Salamony; Dirwan Maya Muchlis; Aloysisa TenyDamayanti Indriastuti (Musamus Journal of Livestock Science, 2020)
Eggs are a food source of poultry animal sources of animal protein that has a delicious taste, easy to digest and highly nutritious. The highest value of eggs is in the yolk, the yolk contains essential amino acids, minerals such as iron, phosphorus and a little calcium and vitamin B complex badly needed by the human body. The weakness of salted eggs is that they have perishable properties so they need to be preserved to maintain their quality. One method used to maintain the quality of salted eggs is the addition of deer fat so that it can improve the taste and have a long shelf life. This research was carried out using quantitative methods and laboratory testing for microbiological observations in a descriptive manner. The results of this study indicate that administration of different deer fat 0.3ml, 0.5ml, 0.7ml from each treatment during 2, 4 and 6 weeks storage. Provision of 0.7 ml deer fat in 4 weeks storage produced good quality in terms of color, texture and ash in salted eggs and no salmonella bacteria were found.